Desenvolvimento de um robô paralelo tipo delta associado com visão computacional para aplicações pick and place - Lazzari, Felipe dos Santos (2012)
This paper presents the development steps of a Delta Parallel Robot whose characteristics make it advantageous on pick and place tasks when compared to serial architecture robots. A prototype was developed to be presented to the academic community in order to gather new findings and improve knowledge, as well as inspiring future endeavors related to this type of device and architecture. To maximize efficiency and precision in “pick-and-place” industrial procedures, this device is associated with the possibility of using computer vision as well as the programming tool LabView.